Existence of a correlation bound s-type anion state of C60 - Voora, Vamsee K.; Cederbaum, Lorenz S.; Jordan, Kenneth D. (The journal of physical chemistry letters, 2013)
It is established using high-level electronic structure calculations that C60 has an s-type correlation-bound anion state with an electron binding energy of about 120 meV. Examination of the “singly occupied” natural orbital of the anion reveals that about 9% of the charge density of the excess electron is localized inside, and about 91% is localized outside the C60 cage. Calculations were also carried out for the HeC60, Ne@C60, and H2O@C60 endohedral complexes. For each of these species, the s-type anion is predicted to be less strongly bound than for C60 itself.